Bahasa Indonesia dan Tantangan Media Sosial Analisis Pustaka Tentang Code-Switching dan Bahasa Campuran di Kalangan Mahasiswa - Angga Ibnu Nugroho; Sri Mulyeni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The phenomenon of code-switching and code-mixing among university students has become increasingly prevalent alongside the rapid growth of social media. This article aims to analyze the challenges and implications of mixed language practices in students’ digital interactions, while reflecting on their significance for the development of the Indonesian language in the global era. The study applies a literature-based analytical approach, using thematic synthesis to identify patterns, motivations, and functions of code-switching across various social media platforms. Findings show that students’ code-switching practices vary depending on the digital ecology of each platform. On Instagram, code-mixing often reflects prestige and modern identity construction. Twitter or X emphasizes communicative efficiency and community solidarity, while TikTok highlights creativity, humor, and stance-taking. The main driving factors include identity expression, practicality, prestige, and online community norms. At a global level, this phenomenon resonates with the trend of digital translanguaging, which broadens the linguistic repertoire of young generations. The study concludes that code-switching in digital spaces presents a dual implication: a potential erosion of Indonesian language norms on one hand, and an opportunity for multilingual enrichment on the other. Therefore, adaptive language policies and digital-linguistic literacy strategies are necessary to safeguard the Indonesian language while embracing creative multilingual practices among students.